Effects of Intergranular Phase and Structure Defect on the Coercivity for the HDDR Nd-Fe-B Bonded Magnet (Journal of Atomic and Molecular Sciences, 2012)
Based on the specific microstructure of HDDR (hydrogenation, disproportionation, desorption, recombination) grains, that the bivariate model concerning the anisotropy constant $K'_1$ and exchange integral $A'_1$ in defect region, which was put forward. Subsequently, the dependence of magnet coercivity on the intergranular phase thickness $d$ and structure defect thickness $r_0$ was studied. The results showed that the coercivity, $H_c,$ increases with increasing $d,$ for the $r_0,$ the anisotropy constant $K_1(0)$ and exchange integral constant $A_1(0)$ at the grain surface taking different values. While $K_1(0)$ and $A_1(0)$ are fixed, $H_c$ enhances with increasing $r_0$ for the same $d.$ On the contrary, for the fixed $r_0$ and $d,$ $H_c$ decreases with increasing $K_1(0)$ or $A_1(0).$ The calculated coercivity is in good agreement with experimental results given by others when $d$ takes 1 nm, $r_0$ is in the rang of 2-5 nm, $A_1(0)$ and $K_1(0)$ change in the range of (0.6-0.7) of $A_1$ and $K_1,$ respectively.